piarepm

## Answered question

2022-01-03

Finding integral:
${\int }_{0}^{1}\frac{\mathrm{ln}\left(1+x\right)}{x}dx$

### Answer & Explanation

Paul Mitchell

Beginner2022-01-04Added 40 answers

Here is an elementary integration of $I={\int }_{0}^{1}\frac{\mathrm{ln}\left(1+x\right)}{x}dx$
$I=-\frac{1}{2}{\int }_{0}^{1}\frac{\mathrm{ln}\left(1+x\right)}{x}dx+\frac{3}{2}{\int }_{0}^{1}\frac{\mathrm{ln}\left(1+x\right)}{x}dx=-\frac{3}{2}{\int }_{0}^{1}\frac{\mathrm{ln}\left(1-x+{x}^{2}\right)}{x}dx$
Let $J\left(a\right)={\int }_{0}^{1}\frac{\mathrm{ln}\left(1-2x\mathrm{sin}a+{x}^{2}\right)}{x}dx$
${J}^{\prime }\left(a\right)=-{\int }_{0}^{1}\frac{2\mathrm{cos}a}{{\left(x-\mathrm{sin}a\right)}^{2}+{\mathrm{cos}}^{2}a}dx=-\left(\frac{\pi }{2}+a\right)$
Then, width $J\left(0\right)={\int }_{0}^{1}\frac{\mathrm{ln}\left(1+{x}^{2}\right)}{x}dx=\frac{12}{I}$
$I=-\frac{32}{J}\left(\frac{\pi }{6}\right)=-\frac{32}{J\left(0\right)+{\int }_{0}^{\frac{\pi }{6}}{J}^{\prime }\left(a\right)da}=-\frac{34}{I}+{\frac{32}{\int }}_{0}^{\frac{\pi }{6}}\left(\frac{\pi }{2}+a\right)da$
which leads to
$I=\frac{{\pi }^{2}}{12}$

sonorous9n

Beginner2022-01-05Added 34 answers

Hint. One may recall that

one may then divide by x and one is allowed to integrate termwise obtaining
${\int }_{0}^{1}\frac{\mathrm{ln}\left(1+x\right)}{x}dx=\sum _{n=1}^{\mathrm{\infty }}{\left(-1\right)}^{n-1}{\int }_{0}^{1}\frac{{x}^{n-1}}{n}=\sum _{n=1}^{\mathrm{\infty }}\frac{{\left(-1\right)}^{n-1}}{{n}^{2}}$
Can you take it from here?

user_27qwe

Skilled2022-01-11Added 375 answers

By integration by parts:
${\int }_{0}^{1}\frac{\mathrm{log}\left(1+x\right)dx}{x}=-{\int }_{0}^{1}\frac{\mathrm{log}x}{1+x}dx=2{\int }_{0}^{1}\frac{-\mathrm{log}x}{1-{x}^{2}}dx-{\int }_{0}^{1}$
but since ${\int }_{0}^{1}\left(-\mathrm{log}x\right){x}^{k}dx=\frac{1}{\left(k+1{\right)}^{2}}$, by expanding $\frac{1}{1-{x}^{2}}$ and $\frac{1}{1-x}$ as geometric series we get:
${\int }_{0}^{1}\frac{\mathrm{log}\left(1+x\right)dx}{x}=2\sum _{kodd}\frac{1}{{k}^{2}}-\sum _{k\ge 1}\frac{1}{{k}^{2}}=\sum _{k\ge 1}\frac{1}{{k}^{2}}$
$=\frac{{\pi }^{2}}{12}$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?